Quality and metabolic implications of including anchovy oil or a blend of herring oil, n-3 PUFA [polyunsaturated fatty acids] concentrate and palm stearin in Atlantic salmon (Salmo salar L.) diets - Menoyo, D.; López Bote, C.J.; Bautista, J.M.; Obach, A. (Spanish Journal of Agricultural Research, 2005)
The effect of feeding Atlantic salmon with two fat sources containing similar concentration of saturated (SAFA), monounsaturated (MUFA) and polyunsaturated (PUFA), but different fatty acid composition, on growth, digestibility, fillet quality and lipid metabolism was studied. Two extruded diets with the same basal composition but coated with herring oil supplemented with palm stearin and n-3 fatty acid concentrate (HO+ diet) or with pure anchovy oil (AO diet) were fed to Atlantic salmon with an average weight of 1.9 kg for 24 weeks. A better growth was reported in fish fed the AO diet (P<0.05). Fat digestibility was affected by dietary fat source, the fish fed the HO+ diet showing a lower apparent digestibility coefficient than those fed the AO diet (88.24 vs. 79.11; P<0.01). Fish fed the AO diet (P<0.004) had a higher lipolytic capacity in the heart. Texture results showed that dorsal muscle from fish fed the AO diet was harder and a negative correlation (P<0.03) was found between peak value and total intramuscular lipids. In conclusion, feeding Atlantic salmon with a fat source rich in 14:0, as opposed to 16:0 and 18:0, resulted in better growth, higher fat digestibility, improved usage of dietary fat as energy fuel and a harder fillet.